Cleft lip and cleft palate: a disease with multiple risk factors in a pregnant woman - Uçar, Mustafa Gazi; İlhan, Tolgay Tuyan; Gül, Ayhan; Sert, Zekiye Soykan; Çelik, Çetin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Clefts of the lip and/or palate (CLP) are currently the most common craniofacial birth defects that arise as a result of failure of facial embryonic processes to fuse. CLP etiology, which involves both genetic and environmental factors, is highly complex; its molecular basis remains largely unknown. In the current study we present a case report of a woman with prenatal diagnosis of cleft lip and palate, who had multiple risk factors including genetics, advanced age, family history, antiepileptic drug usage, consanguineous marriage and smoking. Her previous child was born with CLP, and this also contributes. Data of our study supports the hypothesis of a multifactorial etiology for CLP.